Cosmetic products as an object of technical regulation of the ministry of health. Development of a methodology for the implementation of the technical regulations - Iryna Kazakova (PC Technology Center, 2021)
From 2021, cosmetic products are subject to technical regulation of the Ministry of Health, which is responsible for ensuring the implementation of Technical Regulations, approval of guidelines for their application, national standards in accordance with the requirements of Technical Regulations. It was adopted in early 2021. For the first time in Ukraine, the technical regulations for cosmetic products apply to cosmetic products the principles of technical regulation, powers to comply with which are vested in the relevant Ministry of Health.